Understanding Smoking Behavior in Productive-Age Men: A Survey in Padang City - Abdiana; Masrul; Hardisman; Najirman (proceedinginternational, 2025)
Smoking is still a public health challenge in Indonesia. Nationally, the percentage of the population who smoke has increased from 28.26% in 2022 to 28.99% in 2024. This trend indicates the consistency of smoking habits in society, especially among the productive age group. Men mostly smoke. This can be detrimental to the health of the smoker himself and can also be detrimental to the health of the surrounding environment. There are three important clinical phases in tobacco addiction, namely, trying, sometimes using, and using every day. The purpose of this study was to determine the factors that influence smoking behavior in male adolescents. The method used in this study was a descriptive research type with a population of all productive-age men in Padang City. Sampling used the cluster random sampling technique with a total of 97 respondents. Data were collected through a structured questionnaire that adopted the Global Youth Tobacco Survey (GYTS) instrument. Data were analyzed with a frequency distribution in the form of a percentage. The results showed that 36.1% started smoking at the age of 13 years, the number of cigarettes smoked per day was 1-10 cigarettes (37.1%), the usual place to smoke in public places (30.9%), smoking when gathering with friends (52.6%), Smoking is fun (47.4%), Smoking helps reduce anxiety/anger/restlessness (49.5%), wanting to smoke in the morning immediately after waking up (33%), Getting cigarettes by buying them yourself (55.7%), and the type of cigarette smoked is filtered (39.2%). These findings will inform targeted interventions to reduce tobacco use and promote healthier lifestyles in economically active communities while increasing labor productivity. Keywords: Keywords: age, number of cigarettes, place of Smoking, type of cigarette